BENTUK DAN FUNGSI KALIMAT TANYA DALAM FILM LUCY KARYA LUC BESSON - Lumampak, Billy Marsel Michael; Ranuntu, Garryn Ch.; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
ABSTRACT      This study entitled interrogative sentence in the film Lucy by Luc Besson. In this study the writer identifies, classifies forms,analyzes the fuctions of interrogative sentences in the film Lucy, and finds the most frequently used of interrogative sentences in the film Lucy. The writer uses theory from Aarts and Aarts (1982), Aarts and Aarts say that interrogative sentence is a sentence that contains subjects and open with an auxiliary verb or wh-word. The writer used descriptive method from O’Grady and Dobrovoslky (1992:2), He says that descriptive method will be used to describe and explain the facts that they observe and will not change them. The data of interrogative sentences were taken from skrip of the film Lucy. The result shows that interrogative sentences in the film Lucy have three types those are yes/no question, tag question, and wh-question. According to its fuction in communication, interrogative sentence can be functioned as question and request. The most frequently used of interrogative sentence in the film Lucy is Wh-question.Keywords : Interrogative Sentence, Film Lucy,Syntax Analysis.